Enhancement of Dynamical Coupling in Artificial Spin‐Ice Systems by Incorporating Perpendicularly Magnetized Ferromagnetic Matrix - Syamlal Sankaran Kunnath; Mateusz Zelent; Mathieu Moalic; Maciej Krawczyk (Small Structures, 2025)
Artificial spin‐ice (ASI) systems, consisting of arrays of interacting ferromagnetic nanoelements, offer a versatile platform for reconfigurable magnonics with potential in GHz logic and neuromorphic computing. However, weak dipolar coupling between nanoelements severely limits their functionality. A rich spin‐wave spectrum is numerically demonstrated in an ASI structure immersed in a perpendicularly magnetized ferromagnetic matrix, which is different from a conventional ASI system. A strong magnon–magnon coupling is observed between the bulk second‐order mode of the ASI and the fundamental mode of the matrix, supported by a pronounced anticrossing frequency gap. It is shown that, in addition to the internanoelement dipolar coupling, exchange interactions at the nanoelement‐matrix interface play a crucial role in this hybridization. Furthermore, the strength of the coupling can be enhanced by almost 40% just by reconfiguring the magnetization at the vertices from low‐energy to high‐energy monopole states. These results open the way to exploit ASI systems for magnonic applications, taking advantage of the strong coupling and vertex‐dependent dynamics.